Genome wide identification of MATE and ALMT gene family in lentil (Lens culinaris Medikus) and expression profiling under Al stress condition - Ankita Tripathi; Dharmendra Singh; Jyotika Bhati; Deepti Singh; Jyoti Taunk; Jawaher Alkahtani; Abdulrahman Al-Hashimi; Madan Pal Singh (BMC Plant Biology)
Abstract Background The membrane transporters viz. multidrug and toxic compound extrusion (MATE) and aluminum-activated malate transporter (ALMT) are associated with aluminum (Al) tolerance by accelerating secretion of organic acids, which can influence nutrient availability and stress response. However, such transporter families have not yet been reported in lentil under Al stress condition. Method and results In this study, 90 MATE and 14 ALMT genes were identified and clustered into four (MATE) and five (ALMT) subfamilies/clades with smaller subgroups. All the MATE and ALMT genes were unevenly dispersed across lentil chromosomes. Duplication analysis suggested that LcMATE gene family has expanded primarily through tandem duplication event. Collinearity of lentil with soybean suggested a close relationship between the MATE genes. The MATE promoter regions harboured many stress responsive as well as Al resistance transcription factor 1 related cis-regulatory elements. Predicted 3D (three-dimensional) structure and molecular docking revealed that 5 LcMATE proteins could bind citrate and contain amino acids related to its secretion via citrate exuding motif and other neighbouring sites. Expression analyses of LcMATE and LcALMT genes were performed using quantitative real-time polymerase chain reaction (qRT-PCR). Six genes namely, LcM1, LcM42, LcM46, LcM47, LcALMT8 and LcALMT14 responded to Al stress with varying levels of expression patterns at different time points (3, 6, 12 and 24 h). Conclusion Our findings offer thorough details on the MATE and ALMT transporters in lentils and will aid in valuable understanding for future functional studies of these transporters in generating Al tolerant cultivars.